Nutritional ergogenic aids in cycling: a systematic review - Valiño-Marques, A.; Lamas, A.; Miranda, J. M.; Cepeda, A.; Regal, P. (Nutrients, 2024)
This systematic review aimed to evaluate the effectiveness of the independent or combined use of nutritional ergogenic aids belonging to Group A of the ABCD classification by the Australian Institute of Sport (AIS) in the context of cycling (caffeine, creatine, sodium bicarbonate, beta-alanine, nitrates, and glycerol). A comprehensive search was carried out using three databases: PubMed, Scopus, and Web of Science. All the databases were searched for Randomized Controlled Trials or crossover design studies assessing the effects of supplementation on cycling performance in comparison with placebos in healthy adults. The methodological quality of each study was evaluated using the Physiotherapy Evidence Database scale. Thirty-six articles involving 701 participants were included in this review, examining supplementation with caffeine (n = 5), creatine (n = 2), sodium bicarbonate (n = 6), beta-alanine (n = 3), and nitrates (n = 8). Additionally, supplemental combinations of caffeine and creatine (n = 3), caffeine and sodium bicarbonate (n = 3), caffeine and nitrates (n = 1), creatine and sodium bicarbonate (n = 1), and sodium bicarbonate and beta-alanine (n = 4) were analyzed. A benefit for cyclists` athletic performnce was found when consuming a caffeine supplement, and a potential positive effect was noted after the consumption of sodium bicarbonate, as well as after the combination of caffeine and creatine. However, no statistically significant effects were identified for the remaining supplements, whether administered individually or in combination.